Changes in gross motor function in children with cerebral palsy following repeated intensive rehabilitation periods: a longitudinal study - Opheim, Viktoria; Skagen, Camilla; Tveten, Kine Melfald; Lydersen, Stian; Størvold, Gunfrid Vinje; Sæther, Rannei (Frontiers in Pediatrics, 2025)
PurposeTo evaluate changes in gross motor function in children with cerebral palsy (CP), following multiple intensive rehabilitation periods.Materials and methodsIn this retrospective longitudinal study, we assessed 46 children with CP, aged 2–12 years, Gross Motor Function Classification System (GMFCS) levels I–V. Participants underwent 2–12 intensive rehabilitation periods, incorporating goal-directed group activities. Long-term change in gross motor function was analyzed using a linear mixed model based on reference percentiles for the Gross Motor Function Measure-66 (GMFM-66). Comparisons were made between GMFCS levels and age groups.ResultsGMFM-66 scores increased during each intensive rehabilitation period, with significant improvements in period 1–4. The number of participants decreased as the number of periods increased. GMFM-66 percentiles increased by 10.9 (p < 0.001) per period, with an additive gain of 2.4 (p = 0.124) GMFM-66 percentiles per added intensive rehabilitation period. A decrease in percentiles was observed between periods. Gross motor function enhanced across all GMFCS levels, particularly levels I and V. Children under 6 years showed greater improvements than older children.ConclusionsIntensive rehabilitation may be associated with improved gross motor function in children with CP, irrespective of GMFCS levels. Repeated periods appear especially beneficial in early childhood, supporting their strategic use in long-term rehabilitation.